Perbedaan Tingkat Kelelahan Subyektif Antara Shift Pagi Dan Malam Pada Pekerja Bagian Produksi Pengolahan Beton Di PT. Wijaya Karya Beton Tbk Kabupaten Boyolali - Pamungkas, Usman, Dr. Suwaji, M.Kes, Tarwaka, PGDip Sc, M.Erg (2015)
Shift working often impacts relating to fatigue subjectivein which happened in long term will be chronic fatigue. PT Wijaya Karya Beton enforces morning and night shift for the workers. Night shift workers tend to feel sleepy, thirsty, dizzy, lost concentration and feeling to take rest while working. The aims of this research are to find out the differences of subjective fatigue level between morning and night shift workers in the process of concrete production in PT. Wijaya Tbk. District Boyolali. The research design of this research was analytical observational study which employed cross sectional approach. The sample of this research came from workers, which consist of 106 workers. Data of this research were taken from identity sheet, respondent and measuring fatigue level using KAUPK2 questionnaire. The technique of analyzing the difference used Mann-Whitney statistic test. The result of the research, the score was p< 0,0001 which implied there were differences of subjective fatigue level between morning and night shift workers in the process of concrete production in PT. Wijaya Karya Tbk. District Boyolali. Suggestions for PT. Wijaya Karya Tbk. District Boyolali is providing rest area which is comfortable for the workers